Beginning Relational Data Modeling - Allen, Sharon; Terry, Evan.; SpringerLink (Online service) (Berkeley, CA : Apress, 2005)
Data storage design, and awareness of how data needs to be utilized within an organization, is of prime importance in ensuring that company data systems work efficiently. If you need to know how to capture the information needs of a business system in a relational database model, but don't know where to start, then this is the book for you. Beginning Relational Data Modeling, Second Edition will lead you step-by-step through the process of developing an effective logical data model for your relational database. No previous data modeling experience is even required. The authors infuse the book with concise, straightforward wisdom to explain a usually complex, jargon-filled discipline. And examples are based on their extensive experience modeling for real business systems.
Understanding and Organizing Data: Past and Present -- Introducing Relational Theory -- Understanding Relational Modeling Terminology -- Understanding Data Modeling Methods: Graphical Syntax -- Introducing Object-Oriented Data Modeling -- Examining Levels of Analysis -- How Data Models Fit Into Projects -- Building a Conceptual Model -- Building a Logical Model -- Transforming a Logical Model into a Physical Model -- Designing a Physical Model Only -- Introducing Dimensional Data Modeling -- Reverse-Engineering a Data Model -- Communicating with the Model -- Improving Data Quality and Managing Documentation -- Introducing Metadata Modeling -- Exploring Data Modeling Working Practices.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books